Implikasi Perjanjian Damai Terhadap Aksi Intifadah Hamas - Putri, Gustri Eni (POLITEA, 2020)
This study aims to explain how the implications of the peace agreement as Israel's strategy in reducing the Hamas intifadah action. The discussion in this study is limited to the peace agreement between Israel and the PLO known as the 1993 Declaration of Principles and the intifadah movement in 1987. This research is a qualitative study with a literature study through books, journals, and articles. This study is based on thinking which explains that as a rational actor, the state in taking foreign policy always calculates the cost and benefit. In its foreign policy, the ruling government uses the "optimization of results" criteria. Or in other words, Israel's foreign policy focuses on emphasizing the country's national interests. This rationale influenced Israel's foreign policy, which was to accept a peace agreement with the PLO to reduce the intifadah movement carried out by Hamas. And this policy provides optimal results for the state of Israel.